Sphingolipid Metabolism and Signaling in Skeletal Muscle: From Physiology to Physiopathology - Tan-Chen, Sophie; Guitton, Jeanne; Bourron, Olivier; Le Stunff, Hervé; Hajduch, Eric (Frontiers in Endocrinology, 2020)
Sphingolipids represent one of the major classes of eukaryotic lipids. They play an essentiel structural role, especially in cell membranes where they also possess signaling properties and are capable of modulating multiple cell functions, such as apoptosis, cell proliferation, differentiation and inflammation. Many sphingolipid derivatives such as ceramide, sphingosine-1-phosphate, ganglioside, have been shown to play many crucial roles in muscle under physiological and pathological conditions. This review will summarize our knowledge of sphingolipids and their effects on muscle fate, highlighting the role of this class of lipids in modulating muscle cell differentiation, regeneration, aging, response to insulin, and contraction. We show that modulating sphingolipid metabolism may be a novel and interesting way for preventing and/or treating several muscle-related diseases.